Research on improving polymer pervious concrete mechanical strength by adding EVA to UP resin binder material. (12th December 2022) - Lin, Chen-Han; Yu, Jason
Abstract: Pervious concrete (PC) made of silicate cement has advantages including low cost, low contraction, and high permeability. However, its strength and durability are lower than those of conventional cement concrete. In recent years, the resin composite material is added to the binder material to effectively improve the mechanical properties and durability of permeable concrete. Commonly used resin composites include epoxy and unsaturated polyester (UP). These resin composites are thermosetting, which cure rapidly and feature high strength and durability. The high cost and viscosity of epoxy resin limits its applications. UP is preferable to epoxy due to its lower concentration and price. This study explored the mechanical performance of high-performance PC with UP resin as the binder. Concretes were fabricated with binders of 10%, 30%, and 40% UP resin content, and specimens were mixed with 5–10-mm gravel aggregate. Compression, flexural, and abrasion testing were conducted to determine the specimen durability. The results revealed that the PC with 30% UP resin had optimal performance. UP resin is composed of a straight chain, and although it has excellent rigidity, its ductility is poor. To address this problem, thermoplastic material ethylene–vinyl acetate (EVA) was incorporated into the binder at 10%, 15%, and 20% to improve the ductility. Compression, bending, and abrasion tests showed that the addition of EVA improved the ductility and durability of the samples. Comprehensive experimental results: UP resin was matched with thermoplastic materials; EVA could improve the mechanical properties of small walking bricks with UP resin as the binder material. Durability further promotes the feasibility of a new pavement construction method from the production of a single brick.